HUKUM RIMBA DAN HUKUM MODERN DI KALANGAN ORANG RIMBA DALAM DI JAMBI - Muh. Sohibul Itmam (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2014)
AbstractThis paper describes the dynamics of the mob rule, and modern law inthe social struggles that are changing the legal consciousness as a consequence of interaction with the outside law (modern law). With a qualitative approach, descriptive, analytical, as a field of research that focuses on legal awareness, this paper concludes that there have been major changes in the legal awareness of the jungle which is initially still using ancestral doctrine received from their parents for generations towards accommodating legal and assimilative. The changes areactually the result of a long struggle that typically occur during the transition period leading up to the present reforms. It is thus very possible to occur continuously changes dynamically as the next legal awareness which is influenced by the social context of their conflicts. In addition, the dynamics of legal awareness is certainly supported Jambi provincial government policies and political developments of national law.Keywords: culture, jungle people, mob rule, modern law, awareness law.